Analysis of the Energy Mix of Slovakia in the Context of Improvement of Quality of the Environment - Hlavnova, Barbara; Svitekova, Milena; Simonidesova, Jana (Communications - Scientific letters of the University of Zilina, 2012)
The contribution is focused on the trends of energy balance of Slovakia that is the key indicator determining the consumption of fuelbased energy sources accepting the principles of sustainable development and improving the quality of the environment. It refers to the development of pollutants release from the energy industry in the production of electricity and thermal energy referring to the potential use of RES in the energy mix the composition of which is in direct interaction not only with the development of the environmental load of the components of the environment but also with energy security and energy independence of Slovakia.